The Finisterra-Léon-Mid German Cristalline Rise Domain; Proposal of a New Terrane in the Variscan Chain - Moreira, Noel (2019)
This chapter characterizes the Finisterra Terrane, enhancing its differences from the neighbouring Iberian Terrane. The contact between these terranes is the Porto- Tomar-Ferreira do Alentejo Shear Zone, a major lithospheric structure whose complex Variscan evolution remains debatable. The lithostratigraphic, tectonometamorphic and magmatic features observed in the Finisterra Terrane show that it was an independent terrane during the Devonian. This situation changed during the Mississippian, when the main features of the Finisterra and the Iberian Terranes became similar, which indicates that both terranes evolved together since the Carboniferous times. The similarities of the Finisterra Terrane with the Central European Variscan domains, namely the Léon Block and the Mid-German Crystalline Rise, enable us to propose a new tectono-stratigraphic terrane (Finisterra-León-MGCR Terrane), which defines an arcuate pattern compatible with the Ibero-Armorican Arc.